Aerogel thermal insulation mortar and preparation method thereof

Silica aerosol was prepared by treating the coal gasification slag into porous silicon microspheres and filling their pores with silica aerogel powder to form modified silicon microspheres, and combining other additives to prepare aerogel insulation mortar, silica aerosol was solved by solving the problem of silica aerosol The problem of high glue cost and unused coal gasification slag has achieved low-cost and high-performance insulation mortar.

CN117069462BActive Publication Date: 2025-02-18HUANGSHAN RUISHENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202310835196.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-02-18
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

In the prior art, silica aerogels are costly and can only take effect effectively only at high dosage, resulting in an increase in the cost of insulation mortar and the gasification slag cannot be effectively used as a replacement material.

Method used

Modified silicon microspheres are formed by treating the coal gasification slag into porous silicon microspheres and filling their pores with silica aerogel powder, combining with other additives such as cellulose ether, redispersible latex powder and methyl silicone Sodium acid, prepare aerogel insulation mortar.

Benefits of technology

The thermal conductivity of the insulation mortar is reduced, the compressive strength and waterproof performance are improved, and the production costs are reduced. At the same time, solid waste is effectively utilized and the comprehensive performance of the insulation mortar is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an aerogel thermal insulation mortar and a preparation method thereof, which belong to the technical field of thermal insulation mortars. The aerogel thermal insulation mortar comprises the following raw materials in parts by weight: 70-75 parts of silicate cement, 18-22 parts of fly ash, 3-7 parts of slaked lime, 1-1.4 parts of cellulose ether, 1.8-2 parts of redispersible latex powder, 0.8-1 parts of polypropylene fiber, 1.4-1.6 parts of sodium methyl silicate, 90-100 parts of modified silicon microspheres, and 190-200 parts of water. The aerogel thermal insulation mortar is prepared by the following steps: firstly, silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and modified silicon microspheres are added into a mixer, stirred and mixed to obtain powder, and water is added into the powder, stirred and mixed to obtain the aerogel thermal insulation mortar. The thermal insulation mortar of the invention improves the compressive strength of the thermal insulation mortar and reduces the thermal conductivity, water absorption and production cost of the thermal insulation mortar through reasonable addition of the modified silicon microspheres.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation mortar, and particularly relates to an aerogel thermal insulation mortar and a preparation method thereof. Background Art

[0002] As a material with a three-dimensional nanostructure, silica aerogel has extremely high porosity and a pore size smaller than the free path of air, and its dry density is extremely small. It is an ideal thermal insulation material and can be used to prepare thermal insulation mortar, which can effectively reduce the thermal conductivity of thermal insulation mortar. However, due to technical reasons such as silicon source precursors and drying methods, the cost of silica aerogel is much higher than that of other thermal insulation materials. If only silica aerogel is used as a lightweight aggregate, it will only be effective at a high dosage, which is likely to cause cost increases.

[0003] Coal gasification slag is a solid waste formed after coal is gasified at high temperature and quenched by water in a gasifier. The special formation process makes coal gasification slag have a series of properties such as high reactivity and unique particle morphology, which lays a good foundation for its resource utilization. On the basis of ensuring the performance of thermal insulation mortar, how to treat coal gasification slag and use it in thermal insulation mortar to replace part of silica aerogel aggregate is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The object of the present invention is to provide an aerogel thermal insulation mortar and a preparation method thereof to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] An aerogel thermal insulation mortar comprises the following raw materials in parts by weight:

[0007] 70-75 parts of Portland cement, 18-22 parts of fly ash, 3-7 parts of slaked lime, 1-1.4 parts of cellulose ether, 1.8-2 parts of redispersible latex powder, 0.8-1 parts of polypropylene fiber, 1.4-1.6 parts of sodium methyl silicate, 90-100 parts of modified silica microspheres, and 190-200 parts of water.

[0008] Cellulose ether can improve the uniformity of cement hydration process, reduce the floating of lightweight aggregates and avoid water seepage; redispersible latex powder forms a polymer emulsion after mixing with water, which solidifies, hardens and dehydrates after dispersion to form a continuous polymer network structure, which is intertwined with cement hydration products and can significantly increase the bonding strength between the thermal insulation mortar and the wall; polypropylene fiber can improve the crack resistance of the thermal insulation mortar and avoid the generation and development of internal cracks; sodium methyl silicate, as a hydrophobic agent, reduces the water absorption rate of the thermal insulation mortar, improves the waterproof performance of the thermal insulation mortar, and ensures the stability of the thermal insulation mortar after use.

[0009] Furthermore, the modified silicon microspheres are prepared by the following steps:

[0010] Step A1, adding coal gasification slag to a hydrochloric acid solution with a mass fraction of 35-40%, stirring and mixing at room temperature for 4-6 hours, filtering, washing, and drying, and then transferring to a muffle furnace at a temperature of 600-650° C. and calcining for 3-4 hours to obtain porous silicon microspheres;

[0011] Step A2, adding silica aerogel powder to anhydrous ethanol and dispersing it evenly, then adding porous silicon microspheres, stirring and mixing at a speed of 100-200 r / min for 2 h, filtering and drying in an oven at 80° C. to constant weight, to obtain aerogel-filled silicon microspheres;

[0012] Step A3: After adding the aqueous acrylic emulsion into the sprayer, spray the aerogel-filled silica microspheres and stir continuously to make the aqueous acrylic emulsion evenly cover the surface of the aerogel-filled silica microspheres, and then transfer to a 100-105° C. oven to dry to constant weight to obtain modified silica microspheres.

[0013] Furthermore, the mass ratio of the coal gasification slag to the hydrochloric acid solution is 1:1.3-1.5; the coal gasification fine slag is acid-dissolved in the hydrochloric acid solution to dissolve and separate the metal oxides therein to obtain porous silicon microspheres with a porous and rough surface structure.

[0014] Furthermore, the average particle size of the porous silicon microspheres is 0.1-1 mm, the pore diameter is 1-20 μm, and the silica aerogel can be filled into the pores of the porous silicon microspheres.

[0015] Furthermore, the mass ratio of the porous silicon microspheres, the silicon dioxide aerogel powder and the anhydrous ethanol is 1:0.3-0.5:1-1.5.

[0016] Furthermore, the silica aerogel powder is silica aerogel powder that has been grafted with trimethylchlorosilane and has extremely strong hydrophobic properties.

[0017] Furthermore, the solid content of the aqueous acrylic emulsion is 30-35%, and the mass ratio of the aqueous acrylic emulsion to the aerogel-filled silicon microspheres is 1:1.

[0018] A method for preparing aerogel thermal insulation mortar comprises the following steps:

[0019] First, add silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and modified silicon microspheres into a mixer, stir and mix at a speed of 100-150 r / min to obtain powder, add water to the powder, stir and mix at a speed of 60-100 r / min for 10-15 minutes to obtain aerogel thermal insulation mortar.

[0020] Beneficial effects of the present invention:

[0021] The present invention removes metal oxides in coal gasification slag by acid dissolution with hydrochloric acid solution, and then removes residual carbon in the coal gasification slag by calcination to obtain porous silicon microspheres. When the porous silicon microspheres are directly used as lightweight aggregates, a large amount of brittle fractures and increased water absorption of the porous silicon microspheres will occur, which seriously affects the thermal insulation effect and use effect of the mortar. Therefore, the present invention first uses silica aerogel powder to fill the pores of the porous silicon microspheres, thereby refining the pore size of the porous silicon microspheres and reducing the water absorption of the porous silicon microspheres. Then, a water-based acrylic emulsion is sprayed on the surface of the aerogel-filled silicon microspheres, and a thin adhesive layer is formed after curing to obtain modified silicon microspheres, thereby improving the compressive strength of the porous silicon microspheres as lightweight fillers, effectively avoiding the breakage of lightweight aggregates during the preparation process of the thermal insulation mortar, and ensuring that the thermal insulation mortar has a lower thermal conductivity.

[0022] The present invention uses porous silicon microspheres obtained from solid waste treatment to replace part of the more expensive silica aerogel, which not only reduces the production cost but also brings better use effect. When used together with cellulose ether, redispersible latex powder, polypropylene fiber and sodium methyl silicate, the prepared thermal insulation mortar has excellent comprehensive performance. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment provides a modified silicon microsphere prepared by the following steps:

[0026] Step A1, adding coal gasification slag to a hydrochloric acid solution with a mass fraction of 35%, the mass ratio of coal gasification slag to the hydrochloric acid solution being 1:1.5, stirring and mixing at room temperature for 4 hours, filtering, washing, and drying, and then transferring to a muffle furnace at a temperature of 600° C. and calcining for 4 hours to obtain porous silicon microspheres, the average particle size of the porous silicon microspheres being 0.95 mm;

[0027] Step A2, adding the silica aerogel powder grafted with trimethylchlorosilane into anhydrous ethanol and dispersing it evenly, then adding porous silicon microspheres, the mass ratio of porous silicon microspheres, silica aerogel powder and anhydrous ethanol is 1:0.3:1, stirring and mixing at a speed of 100 r / min for 2 h, filtering and drying in an oven at 80° C. to constant weight, to obtain aerogel-filled silicon microspheres;

[0028] Step A3, after adding an aqueous acrylic emulsion with a solid content of 30% into a sprayer, spray the aerogel-filled silicon microspheres and stir continuously, the mass ratio of the aqueous acrylic emulsion to the aerogel-filled silicon microspheres is 1:1, so that the aqueous acrylic emulsion is evenly covered on the surface of the aerogel-filled silicon microspheres, and then transferred to a 100°C oven to dry to constant weight to obtain modified silicon microspheres.

[0029] Example 2

[0030] This embodiment provides a modified silicon microsphere prepared by the following steps:

[0031] Step A1, adding coal gasification slag to a hydrochloric acid solution with a mass fraction of 38%, the mass ratio of coal gasification slag to hydrochloric acid solution being 1:1.4, stirring and mixing at room temperature for 5 hours, filtering, washing, and drying, and then transferring to a muffle furnace at a temperature of 620° C. and calcining for 4 hours to obtain porous silicon microspheres, the average particle size of the porous silicon microspheres being 0.43 mm;

[0032] Step A2, adding the silica aerogel powder grafted with trimethylchlorosilane into anhydrous ethanol and dispersing it evenly, then adding porous silicon microspheres, the mass ratio of porous silicon microspheres, silica aerogel powder and anhydrous ethanol is 1:0.4:1.3, stirring and mixing at a speed of 150 r / min for 2 h, filtering and drying in an oven at 80° C. to constant weight, to obtain aerogel-filled silicon microspheres;

[0033] Step A3: After adding an aqueous acrylic emulsion with a solid content of 32% into a sprayer, spray the aerogel-filled silicon microspheres with stirring continuously. The mass ratio of the aqueous acrylic emulsion to the aerogel-filled silicon microspheres is 1:1, so that the aqueous acrylic emulsion is evenly covered on the surface of the aerogel-filled silicon microspheres, and then transferred to a 103° C. oven to dry to constant weight to obtain modified silicon microspheres.

[0034] Example 3

[0035] This embodiment provides a modified silicon microsphere prepared by the following steps:

[0036] Step A1, adding coal gasification slag to a hydrochloric acid solution with a mass fraction of 40%, the mass ratio of coal gasification slag to the hydrochloric acid solution being 1:1.3, stirring and mixing at room temperature for 6 hours, filtering, washing, and drying, and then transferring to a muffle furnace at a temperature of 650° C. and calcining for 3 hours to obtain porous silicon microspheres, the average particle size of the porous silicon microspheres being 0.12 mm;

[0037] Step A2, adding the silica aerogel powder grafted with trimethylchlorosilane into anhydrous ethanol and dispersing it evenly, then adding porous silicon microspheres, the mass ratio of porous silicon microspheres, silica aerogel powder and anhydrous ethanol is 1:0.5:1.5, stirring and mixing at a speed of 200 r / min for 2 h, filtering and drying in an oven at 80° C. to constant weight, to obtain aerogel-filled silicon microspheres;

[0038] Step A3, after adding an aqueous acrylic emulsion with a solid content of 35% into a sprayer, spray the aerogel-filled silicon microspheres with stirring continuously, the mass ratio of the aqueous acrylic emulsion to the aerogel-filled silicon microspheres is 1:1, so that the aqueous acrylic emulsion is evenly covered on the surface of the aerogel-filled silicon microspheres, and then transferred to a 105°C oven to dry to constant weight to obtain modified silicon microspheres.

[0039] Comparative Example 1

[0040] Compared with Example 2, in this comparative example, step A2 and step A3 are not performed, that is, the porous silicon microspheres are not subjected to any modification treatment, and the remaining raw materials and steps are the same to obtain porous silicon microspheres.

[0041] Comparative Example 2

[0042] Compared with Example 2, this comparative example does not perform step A2, that is, does not use silica aerogel powder to fill the pores of the porous silicon microspheres, and the remaining raw materials and steps are the same to obtain modified silicon microspheres.

[0043] Example 4

[0044] An aerogel thermal insulation mortar comprises the following raw materials in parts by weight:

[0045] 70 parts of silicate cement, 18 parts of fly ash, 3 parts of slaked lime, 1 part of cellulose ether, 1.8 parts of redispersible latex powder, 0.8 parts of polypropylene fiber, 1.4 parts of sodium methyl silicate, 90 parts of modified silicon microspheres prepared in Example 1, and 190 parts of water.

[0046] The preparation method of the aerogel thermal insulation mortar comprises the following steps:

[0047] First, silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and the modified silicon microspheres prepared in Example 1 were added to a mixer, stirred and mixed at a speed of 100 r / min to obtain a powder, water was added to the powder, and stirred and mixed at a speed of 60 r / min for 15 minutes to obtain an aerogel thermal insulation mortar.

[0048] Example 5

[0049] An aerogel thermal insulation mortar comprises the following raw materials in parts by weight:

[0050] 73 parts of Portland cement, 20 parts of fly ash, 5 parts of slaked lime, 1.2 parts of cellulose ether, 1.9 parts of redispersible latex powder, 0.9 parts of polypropylene fiber, 1.5 parts of sodium methyl silicate, 95 parts of modified silicon microspheres obtained in Example 2, and 195 parts of water.

[0051] The preparation method of the aerogel thermal insulation mortar comprises the following steps:

[0052] First, silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and the modified silicon microspheres prepared in Example 2 were added to a mixer, stirred and mixed at a speed of 120 r / min to obtain a powder, water was added to the powder, and stirred and mixed at a speed of 80 r / min for 12 minutes to obtain an aerogel thermal insulation mortar.

[0053] Example 6

[0054] An aerogel thermal insulation mortar comprises the following raw materials in parts by weight:

[0055] 75 parts of silicate cement, 22 parts of fly ash, 7 parts of slaked lime, 1.4 parts of cellulose ether, 2 parts of redispersible latex powder, 1 part of polypropylene fiber, 1.6 parts of sodium methyl silicate, 100 parts of modified silicon microspheres prepared in Example 3, and 200 parts of water.

[0056] The preparation method of the aerogel thermal insulation mortar comprises the following steps:

[0057] First, add silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and the modified silicon microspheres prepared in Example 3 into a mixer, stir and mix at a speed of 150 r / min to obtain a powder, add water to the powder, stir and mix at a speed of 100 r / min for 10 minutes to obtain an aerogel thermal insulation mortar.

[0058] Comparative Example 3

[0059] Compared with Example 5, this comparative example uses the porous silicon microspheres prepared in Comparative Example 1 to replace the modified silicon microspheres prepared in Example 2, and the other raw materials and steps are the same.

[0060] Comparative Example 4

[0061] Compared with Example 5, this comparative example uses the modified silicon microspheres prepared in Comparative Example 2 to replace the modified silicon microspheres prepared in Example 2, and the other raw materials and steps are the same.

[0062] The thermal insulation mortars prepared in Examples 4 to 6 and Comparative Examples 3 to 4 were made into standard specimens of 70 mm × 70 mm × 70 mm in a mold, dried in an oven at 60° C. to constant weight, and then cooled to room temperature. The thermal conductivity of the thermal insulation mortars was measured according to GB / T 10295; the compressive strength and water absorption of the thermal insulation mortars were measured according to GB / T 5486-2008. The results are shown in Table 1:

[0063] Table 1

[0064] Test items Example 4 Example 5 Example 6 Comparative Example 3 Comparative Example 4 Thermal conductivity W / (m·K) 0.040 0.038 0.037 0.185 0.066 Compressive strength MPa 0.611 0.624 0.636 0.345 0.583 Water absorption % 38 37 37 69 55

[0065] It can be seen from the data in Table 1 that the thermal insulation mortars prepared in Examples 4-6 have excellent thermal conductivity, compressive strength and water absorption, and therefore have the advantages of good thermal insulation performance, excellent performance and low cost; specifically, compared with Comparative Example 3, in Example 5, porous silicon microspheres are directly used as lightweight aggregates, which will cause severe brittle breakage during the mixing process of preparing the thermal insulation mortar, and the pore structure will be reduced, which will cause the thermal conductivity of the mortar to rise sharply, and the compressive strength and water absorption will also be greatly affected; compared with Comparative Example 4, in Example 5, the modified silicon microspheres that have not been modified by filling with silica hydrogel powder have larger pore sizes, and water molecules can easily penetrate the glue layer into the pores, resulting in increased water absorption. The larger pore size also has a negative impact on the heat transfer of the air, which is manifested as an increase in the thermal conductivity of the mortar. The filling of silica hydrogel powder has little effect on improving the compressive strength and can be ignored.

[0066] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An aerogel thermal insulation mortar, characterized in that: It includes the following raw materials in parts by weight: 70-75 parts of Portland cement, 18-22 parts of fly ash, 3-7 parts of slaked lime, 1-1.4 parts of cellulose ether, 1.8-2 parts of redispersible latex powder, 0.8-1 parts of polypropylene fiber, 1.4-1.6 parts of sodium methyl silicate, 90-100 parts of modified silica microspheres, and 190-200 parts of water; The modified silicon microspheres are prepared by the following steps: Step A1, adding coal gasification slag to a hydrochloric acid solution with a mass fraction of 35-40%, stirring and mixing at room temperature for 4-6 hours, filtering, washing, and drying, and then transferring to a muffle furnace at a temperature of 600-650° C. and calcining for 3-4 hours to obtain porous silicon microspheres; Step A2, adding silica aerogel powder to anhydrous ethanol and dispersing it evenly, then adding porous silicon microspheres, stirring and mixing, filtering and drying to constant weight, to obtain aerogel-filled silicon microspheres; Step A3: After adding the aqueous acrylic emulsion into the sprayer, spray the aerogel-filled silica microspheres with constant stirring, and then dry to constant weight to obtain modified silica microspheres.

2. The aerogel thermal insulation mortar according to claim 1, characterized in that: The mass ratio of the coal gasification slag to the hydrochloric acid solution is 1:1.3-1.

5.

3. The aerogel thermal insulation mortar according to claim 1, characterized in that: The average particle size of the porous silicon microspheres is 0.1-1 mm.

4. The aerogel thermal insulation mortar according to claim 1, characterized in that: The mass ratio of the porous silicon microspheres, the silicon dioxide aerogel powder and the anhydrous ethanol is 1:0.3-0.5:1-1.

5.

5. The aerogel thermal insulation mortar according to claim 1, characterized in that: The silicon dioxide aerogel powder is silicon dioxide aerogel powder that has been grafted with trimethylchlorosilane.

6. The aerogel thermal insulation mortar according to claim 1, characterized in that: The solid content of the aqueous acrylic emulsion is 30-35%, and the mass ratio of the aqueous acrylic emulsion to the aerogel-filled silicon microspheres is 1:

1.

7. The method for preparing aerogel thermal insulation mortar according to claim 1, characterized in that: The following steps are involved: First, add silicate cement, fly ash, slaked lime, cellulose ether, redispersible latex powder, polypropylene fiber, sodium methyl silicate and modified silicon microspheres into a mixer, stir and mix at a speed of 100-150 r / min to obtain powder, add water to the powder, stir and mix at a speed of 60-100 r / min for 10-15 minutes to obtain aerogel thermal insulation mortar.

Citation Information

Patent Citations

  • High-performance silicon dioxide aerogel thermal mortar and preparation method thereof

    CN105884313A

  • Utilization method of coal catalytic gasification ash slag

    CN109851255A

Cited By

  • Carbonized high-strength aerogel thermal insulation mortar and preparation method thereof

    CN121591466A